Analysis of the Emergency Medicine Clinical Learning Environment. Issue 3 (20th June 2019) - Ramana Feeser, V.; Zemore, Zachary; Appelbaum, Nital; Santen, Sally A.; Moll, Joel; Aboff, Brian; Hemphill, Robin R.
Abstract: Background: Residencies are grappling with ways to identify methods to internally monitor and improve their learning environments. Building on prior work, the objective of this study was to determine emergency medicine (EM) internal evaluations of perceived organizational support and psychological safety and compare to the results from the Accreditation Council for Graduate Medical Education (ACGME) Resident Survey for the purpose of program improvement and to explore factors affecting residents' perception of their learning environment. Methods: In 2017, the Virginia Commonwealth University School of Medicine Office of Graduate Medical Education and Office of Quality and Safety conducted an in‐person, anonymous safety survey of the residents across 19 residency programs on the Short Survey of Perceived Organizational Support (SPOS) and Psychological Safety Scale (PSS). These were compared to the ACGME Resident Survey for 19 programs. Resident interviews and open response evaluation data informed content analysis on program experiences. Results: Institutional response rates were 63% for the internal learning environment survey and 96% for ACGME Resident Safety Survey. EM residents responded positively on the SPOS and PSS compared to other programs (ranked second highest scores on both scales). One‐hundred percent of respondents agreed or strongly agreed on SPOS items: "Help is available from my department when I have a problem." "My department really cares about my well‐being." "My department values my contribution to its well‐being." Furthermore, EM had the highest overall training experience score (mean = 4.83) on the ACGME survey compared to the 18 other training programs. Qualitative responses suggest program strengths included supportive program leadership, positive working relationships with faculty, and emphasis on trainee wellness. Conclusions: Compared to other programs, EM has created a positive environment of safety and support as perceived by their residents. Internal surveys of the learning environment can help programs understand their culture for purposes of improvement and align with the ACGME survey.